(3cJGH aj Yde GdHjWQIs - (3CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWdj, CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWd,J (B250 (3g` s ((3eMeO Hf eMeO GdSgjdi s)
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO hCgdI hCeG HYO aEfi de CRd HYO eG hgH Gddg di ef GdeYQaI HCdGJ GdaQhSjI s
(3BNQgG (B:s
(3hdPdc bdJ Ef GdPi jZdH Ydjg hLY GdYUH djS HbOQ Cf jYjT hjgdc hGddg CYde HGdUhGH s
(3fSNI NRGFfjI QSe GdCejQ eMeO MhQ GdfGUQi Gdedci GdGTQais
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B145s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs